In God we trust, all others pay cash - Shepherd, Jean (Doubleday, 1966)
Ralph goes back to his hometown of Hohman, Indiana, runs into an old chum, and remembers growing up. An affectionate, wacky, and wryly realistic portrayal of an American family's typical Christmas joys and travails in small-town, Depression-era Indiana. This novel would later serve as the basis for the 1983 movie, A Christmas Story.